HIV-positive persons who inject drugs experience poor health outcomes and unmet needs for care services. Issue 9 (2nd September 2021) - Dasgupta, Sharoda; Tie, Yunfeng; Lemons-Lyn, Ansley; Broz, Dita; Buchacz, Kate; Shouse, R. Luke
ABSTRACT: Comparison of social determinants of health and clinical outcomes between HIV-positive persons who inject drugs (PWID) and HIV-positive persons who do not inject drugs is essential to understanding disparities and informing HIV prevention and care efforts; however, nationally representative estimates are lacking. Interview and medical record data were collected for the Medical Monitoring Project during 2015–2018 among U.S. adults with diagnosed HIV. Among HIV-positive PWID ( N =340) and HIV-positive persons who do not inject drugs ( N =11, 475), we reported weighted percentages and prevalence ratios with predicted marginal means to compare differences between groups ( P <.05). Associations with clinical outcomes were adjusted for age, race/ethnicity, and gender. HIV-positive PWID were more likely to be homeless (29.1% vs. 8.1%) and incarcerated (18.3% vs. 4.9%). HIV-positive PWID were less likely to be retained in HIV care (aPR: 0.85 [95% CI: 0.77–0.94]), and were more likely to have poor HIV outcomes, have unmet needs for care services (aPR: 1.50 [1.39–1.61]), seek non-routine care, and experience healthcare discrimination (aPR: 1.42 [1.17–1.73]). Strengthening interventions supporting (1) continuity of care given high levels of incarceration and housing instability, (2) early ART initiation and adherence support, and (3) drug treatment and harm reduction programs to limit transmission risk may improve outcomes among HIV-positive PWID.